On the stability of Euro area money demand and its implications for monetary policy - Matteo Barigozzi; Antonio Conti (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2013)
We revisit the usefulness of long-run money demand equations for the European Central Bank. We first conduct a model evaluation exercise by means of a recent time-varying cointegration test. A stable relation for euro area M3 is not rejected by data only when accounting for both a speculative motive, represented by international financial markets, and a precautionary motive, proxied by changes in the unemployment rate. Second, relying on this finding, we propose and estimate a novel time-invariant specification for money demand which allows us (i ) to build a leading indicator of stock market busts and (ii ) to describe the anomalous behavior of M3 in the last decade. Excess liquidity matters for both financial and price stability.
Keywords: E41; E52; C32; 330; money demand; time-varying cointegration; price-earnings ratios; unemployment rate; monetary policy